Коррозия и защита арматуры в бетоне - Алексеев Сергей Николаевич (Стройиздат, 1968)
Экземпляры: КХ (20120316) / Инвентарный номер: 447031 / Цена: 0.66 / Сис.шифр: 690.2 / Авт.знак: А 47 / ГРНТИ: 67 / ББК: 38